Copy number variation of two separate regulatory regions upstream of SOX9 causes isolated 46,XY or 46,XX disorder of sex development - Kim, Gwang-Jin; Sock, Elisabeth; Buchberger, Astrid; Just, Walter; Denzer, Friederike; Hoepffner, Wolfgang; German, James; Cole, Trevor; Mann, Jillian; Seguin, John H.; Zipf, William; Costigan, Colm; et al. (Journal of Medical Genetics, 2015)
SOX9 mutations cause the skeletal malformation syndrome campomelic dysplasia in combination with XY sex reversal. Studies in mice indicate that SOX9 acts as a testis-inducing transcription factor downstream of SRY, triggering Sertoli cell and testis differentiation. An SRY-dependent testis-specific enhancer for Sox9 has been identified only in mice. A previous study has implicated copy number variations (CNVs) of a 78 kb region 517-595 kb upstream of SOX9 in the aetiology of both 46,XY and 46,XX disorders of sex development (DSD). We wanted to better define this region for both disorders.By CNV analysis, we identified SOX9 upstream duplications in three cases of SRY-negative 46,XX DSD, which together with previously reported duplications define a 68 kb region, 516-584 kb upstream of SOX9, designated XXSR (XX sex reversal region). More importantly, we identified heterozygous deletions in four families with SRY-positive 46,XY DSD without skeletal phenotype, which define a 32.5 kb interval 607.1-639.6 kb upstream of SOX9, designated XY sex reversal region (XYSR). To localise the suspected testis-specific enhancer, XYSR subfragments were tested in cell transfection and transgenic experiments. While transgenic experiments remained inconclusive, a 1.9 kb SRY-responsive subfragment drove expression specifically in Sertoli-like cells.Our results indicate that isolated 46,XY and 46,XX DSD can be assigned to two separate regulatory regions, XYSR and XXSR, far upstream of SOX9. The 1.9 kb SRY-responsive subfragment from the XYSR might constitute the core of the Sertoli-cell enhancer of human SOX9, representing the so far missing link in the genetic cascade of male sex determination.
EVALuna2:4981